Beyond Emotional Support: The Vital Mediating Role of Knowledge Management in Driving Productivity at PT. Trio Motor. - Rizki, Hafiz; Prima Jaya, Fanlia; Alfiannor, Alfiannor (PT. Hanken Sukses Jaya, 2025)
This study examines the lack of effectiveness regarding the direct impact of organizational support on productivity at PT. Trio Motor Banjarmasin. The primary problem lies in the gap between perceived support and the implementation of a work system capable of directly triggering performance. The objective of the research is to analyze the influence of Perceived Organizational Support (POS) on employee performance, with Knowledge Management (KM) as a mediating variable. The research method utilizes a quantitative approach with a sample of 100 permanent employees. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) via SmartPLS software. The results indicate that POS does not have a significant direct effect on employee performance (p-value 0.390). However, POS significantly affects KM (p-value 0.000), and KM is proven to fully mediate the relationship toward performance (p-value 0.000). In conclusion, organizational support will only result in tangible performance outcomes if channeled through a structured knowledge management strategy. These findings emphasize the importance of integrating a knowledge-sharing culture as a transformation mechanism from support into a competitive advantage.